Sintesis Biodiesel Dari Palm Fatty Acid Destillate (PFAD) Menggunakan Katalis Cu-Hap Dengan Variasi Kecepatan Pengadukan Dan Waktu Reaksi - Putri, Desi Erika; Azis, Yelmida; Alfarisi, Cory Dian (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
This research will shown the effect of stirring velocity and reaction time to biodiesel yield production and determine the physical and chemical characteristics of biodiesel. Palm fatty acid destillate (PFAD) synthesis which is a by-product of cooking oil processing becomes biodiesel through esterification. The esterification was done by mixing PFAD by 25 gram with Cu-HAp catalyst 0.25 gram and 97 ml methanol. Stirring velocity is 250 rpm, 300 rpm and 350 rpm and reaction time variation is 2 hours, 3 hours and 4 hours at 60 ° C. The highest biodiesel yield at 300 rpm stirring speed with a reaction time of 2 h is 63%. For physics characteristic of biodiesel in the form of density are: 0,884 gr/ml - 0,902 gr/ml, viscosity: 4,181 cSt - 5,029 cSt, acid number: 0,553 mg KOH/g oil - 1,661 mg KOH/g oil and calorific value: 9048 - 9813 Kcal / kg produced according to biodiesel standards SNI-04-7182-2006. For the analysis of GC-MS (Gas Chromatography-Mass Spectroscopy) the main compounds found in biodiesel from PFAD are methyl myristate, methyl palmitate, methyl linoleate, methyl oleate and methyl stearate is 78,88%Keywords: Biodiesel, PFAD, Cu-HAp catalyst, esterification.